Analisis Pengaruh Faktor Kebudayaan, Sosial, Pribadi, dan Psikologis terhadap Keputusan Pembelian Makanan Cepat Saji pada Konsumen Kentucky Fried Chicken (KFC) Walikota Medan - Millatina Urfana; Beby Karina Fawzeea Sembiring (Jurnal Media Informasi Manajemen, 2013)
Abstract The purpose of this research is to define and analyze the influence of cultural, social, personal, and psychological factor to fast food purchasing decision. This research was conducted to Kentucky Fried Chicken (KFC) Walikota Medan consumers. The kind of this research is explanatory that purposes to analyze the relationship between a variable with other variables or how a variable influences others. The data analysis methods used are descriptive and quantitative method and linear multiple regression. The data used are primary and secondary data. The primary was from questionnaire that was given to respondent. The secondary were from books, journals, earliest studies, and information that was from internet. This research used 100 respondents as samples. The results showed that cultural, social, personal, and psychological have a positive and significant influence on fast food purchasing decision of Kentucky Fried Chicken (KFC) Walikota Medan consumers. It could be known from the results of simultaneous linear regression test. Based on the significant test partially, that personal and psychological factor influenced positively and significantly on purchasing decision. The cultural factor influenced positively but not significant. The social factor influenced negatively and not significant. The dominant variable that influenced partially to purchasing decision is psychological factor. Keywords: cultural, social, personal, psychological, and purchasing decision.